2014
DOI: 10.1242/jeb.101113
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned discrimination of magnetic inclination in a spatial-orientation arena task by homing pigeons (Columba livia)

Abstract: It has been well established that homing pigeons are able to use the Earth's magnetic field to obtain directional information when returning to their loft and that their magnetic compass is based, at least in part, on the perception of magnetic inclination. Magnetic inclination has also been hypothesized in pigeons and other long-distance navigators, such as sea turtles, to play a role providing positional information as part of a map. Here we developed a behavioral paradigm which allows us to condition homing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…This is also consistent with reports that suggest it was not static magnetic field but its gradient that was more important for induction of analgesia [Kiss et al, ]. Also it has recently been shown that pigeons can detect changes in a static magnetic field inclination, which would correspond to an induced ELF if magnetic field detector was at a fixed inclination [Mora et al, ]. Currently, we are attempting to investigate this possibility by introducing static magnetic field of differing gradient strengths into the shielded environment.…”
Section: Contributions Madesupporting
confidence: 88%
“…This is also consistent with reports that suggest it was not static magnetic field but its gradient that was more important for induction of analgesia [Kiss et al, ]. Also it has recently been shown that pigeons can detect changes in a static magnetic field inclination, which would correspond to an induced ELF if magnetic field detector was at a fixed inclination [Mora et al, ]. Currently, we are attempting to investigate this possibility by introducing static magnetic field of differing gradient strengths into the shielded environment.…”
Section: Contributions Madesupporting
confidence: 88%
“…Juvenile migrants that had not yet established a navigational map also oriented WSW at the capture site but became randomly oriented when the magnetic declination was shifted 8.5 . In combination with latitudinal cues, which birds are known to detect and use [10][11][12], magnetic declination could provide the mostly east-west component for a true bi-coordinate navigation system under clear skies for experienced migratory birds in some areas of the globe.…”
Section: Discussionmentioning
confidence: 99%
“…Spring migration of pied flycatchers in these regions is recorded mainly in the second ten days of May, but first birds may be seen from the very end of April [39,40]. The possible periods of imprinting (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and spring arrival (6-20 May) of pied flycatchers are included in the periods we analysed in this paper (July-August and April-May).…”
Section: Site Fidelity In Northeast Europementioning
confidence: 99%
“…The ability of birds and sea turtles to perceive both total intensity and inclination of Earth-strength magnetic fields has been shown experimentally [21][22][23][24]. If birds [25], sea turtles [15,26,27], possibly also salmonid fishes [28,29] and other long-distance migrants use the geomagnetic field for position finding, the question inevitably arises: what is the possible accuracy of the geomagnetic map?…”
Section: Introductionmentioning
confidence: 99%